2019
DOI: 10.2174/1871520619666190408142131
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of CSN6 in Biological Behavior and Cancer Progress

Abstract: Background: The Constitutive Photomorphogenesis 9 (COP9) signalosome (CSN) subunit 6 (CSN6) noticeably acts as a regulator of the degradation of cancer-related proteins, which contributes to cancerogenesis. The aims of this paper are to expound the research advances of CSN6, particularly focusing on roles of CSN6 in the regulation of biological behavior and cancer progress. Methods: Literature from PubMed and Web of Science databases about biological characteristics and application of CSN6 published in recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…The high mortality rate of liver cancer is mainly associated with tumor invasion, metastasis and tumor recurrence after surgical resection (6,37). In recent years, a number of studies have confirmed that the CSN superfamily is widely involved in the regulation of several important intracellular pathways, including cell proliferation, migration, invasion and signal transduction, and plays an important role in tumor development (13,(38)(39)(40). For example, CSN5 and CSN6 are highly expressed in myeloma, lung, colon, breast cancer, malignant glioma and leukemia clinical tissues (14).…”
Section: Discussionmentioning
confidence: 99%
“…The high mortality rate of liver cancer is mainly associated with tumor invasion, metastasis and tumor recurrence after surgical resection (6,37). In recent years, a number of studies have confirmed that the CSN superfamily is widely involved in the regulation of several important intracellular pathways, including cell proliferation, migration, invasion and signal transduction, and plays an important role in tumor development (13,(38)(39)(40). For example, CSN5 and CSN6 are highly expressed in myeloma, lung, colon, breast cancer, malignant glioma and leukemia clinical tissues (14).…”
Section: Discussionmentioning
confidence: 99%